Reviewing the situation: practitioner perspectives on the use and effectiveness of 28-day homicide reviews. Issue 3 (16th September 2019) - Hill, Stewart; O'Neill, Martin
Abstract : Purpose: The purpose of this paper is to report a study of practitioner views on the 28-day homicide review process. Design/methodology/approach: The research draws upon primary data from interviews with senior investigating officers (SIOs) engaged in homicide investigations and review officers tasked with reviewing homicides unsolved after 28 days. Findings: The review process was perceived to be meeting the needs of the organization but adding little, or no direct value to SIOs. Despite this, there was agreement as to the potential value and necessity of the homicide review process. Issues such as the purpose and process of reviews were considered, with recommendations providing impetus for the Metropolitan Police Service (MPS) to review the use of reviewers commensurate with their expertise, the training and development of reviewers, and the aims, format and timing of a review. Research limitations/implications: The study involved the MPS, and its relevance to review processes elsewhere, whilst likely, is unproven. Further research could identify whether similar issues arise elsewhere, although the findings of this study could encourage other forces to undertake internal reviews of their own systems and processes to understand whether improvements could be made. Whilst over a third of the SIOs and Murder Investigation Team managers took part in the study, a fifth of the review officers were interviewed. Practical implications: MPS should amend the objectives of a MCR to reflect the role they play in the prevention of miscarriages of justice. The MPS should conduct a skills analysis of existing staff. Reviewers should be appointed to cases within their sphere of expertise, and should all be qualified at Professionalising the Investigative Process (PIP) Level 3. The MPS should consider an arbitration process for contested review recommendations. The College of Policing should consider a PIP development programme for proactive SIOs. The College of Policing should review and support SIO continuing professional development opportunities within the MPS. Originality/value: The findings are relevant to any police service currently undertaking 28-day reviews of unsolved homicide investigations.